The Transmission of ULF Waves From the Solar Wind to the Magnetosphere: An Analysis of Some Critical Aspects - Villante, U.; Recchiuti, D.; Di Matteo, S. (Frontiers in Astronomy and Space Sciences, 2022)
Several critical aspects may influence the analysis of the relationship between the solar wind (SW) and magnetospheric fluctuations, for example, the characteristics and frequency of SW fluctuations that are expected to impinge the magnetosphere may not be the same when they are observed by spacecraft located at different places in front of the magnetosphere; similarly, the choice of analytical methods adopted for the spectral analysis might influence the frequency estimate (as well as the wave identification itself) both in the SW and magnetosphere. Focusing our attention on these aspects, we present an analysis of SW compressional fluctuations (f ≈ 1–5 mHz), following two interplanetary shocks observed by two interplanetary spacecraft, regarded as two different situations in terms of spacecraft separation and distance from the magnetosphere. Our results show that some differences in the characteristics of SW fluctuations emerge when the same stream is observed at different places and confirm the critical role of analytical methods in determining fluctuation characteristics. We compared aspects of SW fluctuations with those of magnetospheric fluctuations following the sudden impulses due to the impact of interplanetary shocks. For this scope, we examined observations by two satellites at geostationary orbit and at several ground-based stations. We found that the magnetospheric fluctuations were related to compressional SW fluctuations approximately at the same frequencies, with no evidence for wave activity of internal origin or directly driven by the shock impact.